An ultra-high performance concrete incorporating viscosity-controlling agent: Fiber distribution and microstructure - Zhao, Baojun; Zhang, Zongjun; Wu, Chen; Zou, Changgen; Xu, Xin; Yang, Han; Zhang, Wenqi (Frontiers in Materials, 2023)
In order to realize the stability of steel fiber inside ultra-high performance Concrete (UHPC) under vibration and improve the use efficiency of fiber, bentonite is used as auxiliary cementitious material in this study. The influence of bentonite dosage on the mechanical properties of UHPC matrix and the mechanical properties and microstructure of ultra-high Performance fiber Reinforced Concrete (UHPFRC) is explored. On this basis, the functional relationships between the distribution and orientation of steel fibers, the freshness of the matrix and the rheological parameters of UHPC are established, and the evaluation model of the service efficiency of steel fibers is established. The results show that with the gradual increase of bentonite incorporation, the use efficiency of UHPFRC steel fiber increases first and then decreases, and when the cement content of bentonite was 2.5%, 5.0%, 7.5% and 10.0%, the flexural strength of UHPFRC increased by 9.0%, 17.6%, 18.5% and 6.1%, respectively. In addition, the increase of bentonite content will lead to the continuous decrease of the fluidity of fresh UHPC slurry (from 261mm to 100mm). When the bentonite content is 10.0%, the UHPC slurry has almost no fluidity (100mm), which leads to the appearance of pores in the UHPC matrix and the decrease of compressive strength.